In search of sasquatch - Halls, Kelly Milner, 1957- (Houghton Mifflin Books for Children, 2011)
"Sasquatch, also known as Bigfoot, is considered a cryptid--a creature of cryptozoology. What is cryptozoology? According to author and cryptozoologist Loren Coleman, it is the study of creatures not formally recognized by traditional science. It is the quest to understand eyewitness observations that simply cannot be proven via ordinary channels. Coined by French-born zoologist Dr. Bernard Heuvelmans in the 1960s, the term "cryptozoology" is based on the Greek word "kryptos," which means "hidden." It's a perfect definition for a sometimes imperfect set of scientific goals. Why imperfect? Because "hidden" animals are hard to find, hard to believe in, and, if you're not the person who had the close encounter, hard to prove. Science depends on evidence--careful and repeated documentation. And not everyone believes a creature like Sasquatch is real. Serious Sasquatch hunters are as skeptical as unbelievers. They are not out to collect great stories. They are out to put together facts. Proof. The difference is, they are willing to keep an open mind. Sasquatch and its cousins around the world have escaped capture so far, but other mysterious animals once considered cryptids (undocumented mystery animals)--such as the giant squid and coelacanth--have eventually been confirmed. So as long as cryptids leave trails of scattered clues, cryptozoologists will keep trying to put the puzzle pieces together, especially when it comes to Sasquatch. In In Search of Sasquatch, author Kelly Milner Halls interviews cryptozoologists, linguistics experts, anthropologists, biologists, and regular people like you and me who have seen, heard, or maybe stumbled across evidence leading them to believe that Sasquatch is real. Native Americans had hundreds of names for this huge, mysterious creature of the night. There is a famous video showing something that experts claim is NOT a man in a costume. And then there's the Navy linguistic expert whose analysis of some noises heard at night will make your head spin. Do you believe in Sasquatch? You just might after reading this book!"--Provided by publisher.